1949
DOI: 10.1128/jb.57.1.67-71.1949
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity Studies of Bacterial Suspensions

Abstract: In recent physical-chemical studies of the bacterial cell little attention has been devoted to the effect of concentrated cell suspensions on the ability of the suspending medium to conduct an electric current. Oker-Blom (1912) reported

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1951
1951
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…2). It has been earlier observed that an increase in conductivity is proportional to the corresponding decrease in cells in a suspension thus con rming the decrease in suspended bacterial cells (Harris and Patty, 1949).Furthermore, honeytrap indicated that the strip has a percent reduction value of 96% and a log reduction equivalent to 1.6.…”
Section: Attraction Of Cell By Shsmentioning
confidence: 77%
“…2). It has been earlier observed that an increase in conductivity is proportional to the corresponding decrease in cells in a suspension thus con rming the decrease in suspended bacterial cells (Harris and Patty, 1949).Furthermore, honeytrap indicated that the strip has a percent reduction value of 96% and a log reduction equivalent to 1.6.…”
Section: Attraction Of Cell By Shsmentioning
confidence: 77%
“…However, Frampton and Hildebrand (1944) reported from electrophoresis studies that washing in distilled water did not markedly alter the cell surfaces. Harris and Patty (1949) have indicated that similarly treated organisms were in a viable condition following such treatment.…”
Section: Resultsmentioning
confidence: 99%